(untitled) (Gaceta Técnica, 2023)
In many cases, the infrastructures planned at the beginning of the 20th century originally had studies of important needs, occupying strategic locations and providing services that, even after the latest advances in technology, have remained unanswered in the 21st century. In other cases, buildings and infrastructure gained importance in traditional use, in the social imagination or as a meeting place for the population, being attractive for reopening with the same or very different uses. The reflection of those who study the history of our infrastructures is, therefore, deserved, since its reason for being usually covers a calm and reflective study of interesting places, necessary connections and strategic uses, and that the development fever made us, in many cases, forget.